Protocol for high-yield bacterial expression and purification of the voltage-dependent anion channel 1 for high-throughput biophysical assays - Stefano Conti Nibali; Andrea Magrì; Angela Messina; Armin Wagner; Ramona Duman; Vito De Pinto; Cristian Turato; Cristina Arrigoni; Marco Lolicato (STAR Protocols, 2025)
Summary: Voltage-dependent anion channel 1 (VDAC1) is a key protein in cellular metabolism and apoptosis. Here, we present a protocol to express and purify milligram amounts of recombinant VDAC1 in Escherichia coli. We detail steps for a fluorescence polarization-based high-throughput screening assay using NADH displacement, along with procedures for thermostability, fluorescence polarization, and X-ray crystallography. In this context, we demonstrate how 2-methyl-2,4-pentanediol (MPD), a crystallization reagent, interferes with VDAC1 small-molecule binding, hindering the detection of these ligands in the crystal.For complete details on the use and execution of this protocol, please refer to Conti Nibali et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.